A Poet's Love (Dichterliebe) : a cycle of songs [Bladmuziek] - Schumann, Robert; Heine, Heinrich (London : Novello and Company.)
Bibliotheek Camille Huysmans
Dedicator: Raskin, Maurice, dedicatee: Huysmans, Camille
Engels
Duits
Partituur
Keywords: liedcycli; klassieke liederen; partituren